1989
DOI: 10.2190/kkp0-w3q5-6rdn-rxyt
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Decline in Postural Control Mechanisms

Abstract: In order to study voluntary and reflexive mechanisms of postural control, young and elderly persons were given large-fast and small-slow ankle-rotation postural disturbances while standing on a movable platform capable of measuring ground reaction forces. Large-fast rotations were employed to activate long-loop reflexes, and small-slow rotations were employed to tap the higher level sensory integration aspects of postural control. Overall, the elderly persons exhibited more perturbation induced sway and showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 24 publications
4
82
3
Order By: Relevance
“…It has been reported that postural control adaptability under unusual conditions of sensory stimulation is markedly decreased in elderly subjects Woollacott et al, 1986;Stelmach et al, 1989;Allison et al, 2006). Moreover, the literature also suggests that the cerebellum and basal ganglia are closely involved in postural control adaptability (Traub et al, 1980;Chong et al, 1999;Earhart et al, 2002;Rocchi et al, 2002).…”
Section: Age-related and Gender-related Differences In Adaptability Omentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that postural control adaptability under unusual conditions of sensory stimulation is markedly decreased in elderly subjects Woollacott et al, 1986;Stelmach et al, 1989;Allison et al, 2006). Moreover, the literature also suggests that the cerebellum and basal ganglia are closely involved in postural control adaptability (Traub et al, 1980;Chong et al, 1999;Earhart et al, 2002;Rocchi et al, 2002).…”
Section: Age-related and Gender-related Differences In Adaptability Omentioning
confidence: 99%
“…From the perspective of equilibrium training to prevent falls, evaluating postural control adaptability in the elderly is extremely important. Although it has been reported that adaptability of postural control to new environmental contexts is impaired in the elderly Woollacott et al, 1986;Stelmach et al, 1989;Allison et al, 2006), the relationship of this deterioration to increasing age and to gender has not been investigated systematically. Nashner (1976) observed an adaptive adjustment, involving the gradual reduction of response in the stretched triceps surae, in standing subjects exposed to repeated toe-up floor inclinations.…”
Section: Introductionmentioning
confidence: 99%
“…Increased fall risk in older adults has been attributed to a variety of sensory, motor, cognitive, environmental, and medical factors (Moreland et al, 2003;Myers et al, 1996;Northridge et al, 1995). In particular, many aging-related changes in the postural responses used to maintain and regain balance have been identified McIlroy and Maki, 1996;Mille et al, 2003;Stelmach et al, 1989). However, the mechanisms whereby older adults actually fall following a loss of balance have been little investigated (Lockhart et al, 2003;Pavol et al, 2001;Pijnappels et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This aspect of balance control can be tested by inducing body sway in standing subjects by sudden support surface translation [10,11]. Changes in postural responses following support surface translation were found to occur with ageing and could possibly lead to delayed, insufficient or inappropriate attempts at balance recovery [12][13][14][15][16]. However, in addition to older adults, altered reactive postural responses have also been observed in healthy young adults who were experimentally deprived of normal somatosensory function, and in patients with vestibular dysfunction or peripheral neuropathy [14,15,17,18].…”
Section: Introductionmentioning
confidence: 99%